How to Grow and Survive without Zinc Oxide in Pig Production? A Comparative Study with STODI (Global Journal of Medical Research, 2022)
During weaning, piglets are exposed to a range of stressors, all of which cause gastrointestinal and immune system issues. Post-Weaning Diarrhoea (PWD) is a multifactorial illness characterized by the frequent secretion of watery faeces, which can cause stunt growth, morbidity, and even death. STODI ® is the most incredible option for ZnO to reduce PWD and increase pig growth performance in the first few weeks after weaning. STODI ® is a polyherbal combination including Acacia nilotica, Andrographis paniculata, Holarrhena antidysenterica, Punica granatum, and Terminalia bellirica. This can lower the incidence of diarrhoea and promote the growth of the piglet.
Keywords: piglet; post-weaning diarrhoea; STODI® and ZnO